1978
DOI: 10.1161/01.cir.57.4.699
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of echocardiography in assessing left ventricular dimensions and volume.

Abstract: The accuracy of determining left ventricular function from echocardiography was assessed in 26 children (group I) with cineangiographically-determined normal left ventricular volume (LVV) and 28 children (group II) with large left ventricular volumes. Conventional LV echo dimensions were compared to the cineangiographic LV anterior-posterior minor axis (LVmA) and LVV. Very good correlations were found in group I between LV end-diastolic echo dimensions (LVEDD) and cine LVmA (r = 0.91) and between LVEDD and LV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Despite an apparent increase in the rate of symptomatic HIV associated left ventricular dysfunction compared with the general population, the small number of cases arising from clinical referrals suggests that morbidity or mortality caused by contractile dysfunction in an HIV infected population is still relatively infrequent 8. Velocity of circumferential fibre shortening was negatively connected with haemoglobin concentration, and it was the only indicator of left ventricular systolic function that was abnormal in the HIV infected population—this variable may not, however, be reliable when there is significant left ventricular dilatation,21 as observed in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an apparent increase in the rate of symptomatic HIV associated left ventricular dysfunction compared with the general population, the small number of cases arising from clinical referrals suggests that morbidity or mortality caused by contractile dysfunction in an HIV infected population is still relatively infrequent 8. Velocity of circumferential fibre shortening was negatively connected with haemoglobin concentration, and it was the only indicator of left ventricular systolic function that was abnormal in the HIV infected population—this variable may not, however, be reliable when there is significant left ventricular dilatation,21 as observed in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…The vagaries in the subjective measurements of echocardiograms has been discussed [17]. However, prior studies [18][19][20] have demonstrated that echocardiography compares favorably with direct intracardiac assessment of cardiac function in lionarteriosclerotic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative assessment of left ventricular (LV) size is a fundamental aspect of routine echocardiography in adults and children 1,2 . The subxiphoid “bullet” (5/6 area × length) method of LV end‐diastolic volume estimation has potential advantages over LV end‐diastolic dimension derived by M‐mode echocardiography in certain circumstances such as LV volume overload, abnormal ventricular septal position, 3 and inadequate parasternal acoustic windows. It is based on the assumption that the LV can be modeled as a prolate ellipse, an assumption that has been validated by previous work, especially with regard to its diastolic shape in vivo 4 .…”
mentioning
confidence: 99%